THE ROLE OF THE ENDOMETRIAL MICROBIOME IN INFERTILITY AND REPRODUCTIVE HEALTH: CURRENT EVIDENCE AND FUTURE DIRECTIONS - Klaudia Dybalska; Mateusz Kęska; Michael Platschek; Anna Barbara Tuleja; Michał Drabik; Julia Kosmulska; Maksym Sikora; Sylwia Wiktoria Kolano; Jakub Nowak; Karol Józef Szkarłat (International Journal of Innovative Technologies in Social Science, 2025)
Infertility affects 10–12% of couples and growing evidence implicates the reproductive tract microbiome in implantation success. This narrative review synthesizes human studies on the vaginal and uterine (endometrial) microbiota in relation to fertility outcomes and mechanistic markers. We searched PubMed/MEDLINE, Embase, and Scopus (2000–30 Oct 2025) for randomized and observational studies reporting implantation, clinical pregnancy, live birth, or relevant biomarkers (e.g., α/β-diversity, inflammatory cytokines, LIF). Data were summarized descriptively due to heterogeneity in sampling, sequencing pipelines, and outcome definitions. Across studies, the uterine cavity is no longer viewed as sterile and typically shows low-biomass, often Lactobacillus-lean communities distinct from the vagina. Dysbiosis—frequently characterized by reduced Lactobacillus dominance and increased anaerobes—has been associated with lower implantation and clinical pregnancy rates and with inflammatory profiles that may suppress LIF. Limited interventional data suggest that targeted therapies (e.g., probiotics or antibiotics followed by probiotics) can restore eubiosis in some patients and may improve implantation, but evidence remains preliminary and at risk of bias. We conclude that microbiome composition is plausibly linked to implantation and early pregnancy outcomes, yet clinical adoption is premature. Standardized sampling, rigorous contamination control, multi-omic profiling, and well-powered randomized trials are needed to define actionable thresholds and therapeutic strategies.